Respuesta :
Answer:
Option A.
Step-by-step explanation:
It is given that
[tex]j=-2, k=-1[/tex]
The given expression is
[tex]\left(\dfrac{jk^{-2}}{j^{-1}k^{-3}}\right)^3[/tex]
Substitute the given values in the above expression.
[tex]\left(\dfrac{(-2)(-1)^{-2}}{(-2)^{-1}(-1)^{-3}}\right)^3[/tex]
[tex]\Rightarrow \left(\dfrac{(-2)(1)}{\dfrac{1}{-2}(-1)}\right)^3[/tex]
[tex]\Rightarrow \left(\dfrac{-2}{\dfrac{1}{2}}\right)^3[/tex]
[tex]\Rightarrow \left(-4\right)^3[/tex]
[tex]\Rightarrow -64[/tex]
Therefore, the correct option is A.
Answer:
The answer is A.
Step-by-step explanation:
I did the test, and I also solved it. Its the only logical answer.